PERANCANGAN BUKU CERITA BERGAMBAR KISAH ORANG RANTAI DI KOTA SAWAHLUNTO - Titiany Titiany; syafwan syafwan (Universitas Negeri Padang, 2020)
Sawahlunto City is a tourism city that presents historical tourism of former mining. The city holds a bitter story experienced by prisoners who are employed like slaves called Chain People to dredge coal. The purpose of this design is to produce a design book illustrated by the story of PEOPLE CHAIN in Sawahlunto City as a source of knowledge for high school students and tourists. To create an interesting picture book, the designer uses illustration theory, book design theory, and picture story book theory. The designer conducts research and collects data by observing and studying literature. The data will be used as reference data in making illustrations and text stories. The designer uses the concept of glassbox as a design method.In addition to illustrated story books as the main media, in the design of this final work the authors use supporting media such as e-books, backdrops, posters, bookmarks, notebooks, totebags, brochures and stickers.Keywords : Illustration book, illustration, Orang Rantai , Sawahlunto